Assessing Self-Stigma of Help-Seeking in Student Veterans: A Psychometric Validation Study. Issue 3 (3rd July 2022) - Eagle, Daniel R.; Iwanaga, Kanako; Kaya, Cahit; Muller, Veronica; Lee, Beatrice; Rumrill, Stuart; Chiu, Chung-Yi; Tansey, Timothy N.; Chan, Fong
ABSTRACT: Transition from regimented military life to a less structured college life can pose considerable challenges for student veterans. However, student veterans may be reluctant to seek psychological help because of the help-seeking stigma in the military culture. The present study investigated the measurement structure, reliability, and validity of the Self-Stigma of Seeking Help Scale in a sample of student veterans in the United States. Exploratory factor analysis revealed a two-factor measurement structure: (a) feeling of inadequacy, and (b) threat to self-confidence with relevant internal consistency reliability and construct validity. In the present study, feeling of inadequacy was found to be associated with interpersonal relationship problems, alcohol, and drug use problems, and depression, while threat to self-confidence was found to be associated with alcohol and drug use problems only. Implications for outreach services and the use of positive psychology interventions to lessen the stigma associated with seeking help are discussed.